Mathematical models of biological objects multiplication and growth - Bartaševičius, Algimantas; Lapinskas, Antanas; Didžgalvis, Rimantas (Lietuvos matematikos rinkinys, 2004)
Object under analysis is general biological type. The parameters, that is limited by biological code and making dependant on multiplication and growth processes of biological type, are formalized with scalar matrixes. External influences are formalized with scalar functions' matrixes of vector arguments. Multiplication and growth process mathematical models of general biological type have been made. These models are oriented into their calculation within simulation modeling system SIMULINK.
Keywords: biological type; multiplication; growth; mathematical modeling; simulating modeling